Incorporation of stingless bee honey into hydrogel as a potential wound healing treatment - Kasmuri, Abdul Razak; Ab. Hadi, Hazrina (2019)
Honey is a well establish treatment for wound healing due to its antimicrobial, antioxidants, anti-inflammatory and high sugar contents. In this project, the stingless bee-based hydrogel formulation was developed and characterized. Response surface model (RSM) which is consist of factorial design and central composite design was used to develop and optimized the hydrogel. The antimicrobial effects of the stingless bee honey can be observed in 30% v/v, 40% v/v, 50% and 100% v/v concentrations where there were zones of inhibition formed in the respective bacteria colonies. From the antimicrobial evaluation, stingless bee honey has the ability to inhibit the growth of pathogenic P. aeruginosa and S. aureus from 30% v/v concentration until fully 100% pure concentration. When incorporated into the hydrogel, the formulation developed also has this antimicrobial activity without compromising the value of the honey. The developed hydrogels themselves free from pathological microorganism that could further infected the skin based on the result from microbial limit test. For raw macrophages culture test, stingless bee honey did not show any significance changes toward the production of pro-inflammatory cytokines. The possible explanation is due to the immunomodulator properties of the honey where it has the ability to balance the production of pro-inflammatory cytokines when the level of cytokines is reduced or upsurge. In conclusion, the stingless bee honey as a natural wound healing promoter was successfully developed into an advanced pharmaceutical dosage form, hydrogel.